SANTOS REGO, M. A. (Ed.) (2020). La Transferencia de Conocimiento en Educación. Un desafío estratégico. Madrid: Narcea, 229 páginas, ISBN 978-84-277-2681-9 - Carmen Palmero Cámara (Universidad de La Rioja, 2020)
SANTOS REGO, M. A. (Ed.) (2020). La Transferencia de Conocimiento en Educación. Un desafío estratégico. Madrid: Narcea, 229 páginas, ISBN 978-84-277-2681-9.